2022
DOI: 10.3390/ijerph20010769
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence and Self-Rated Aggression of Adolescents during the First Wave of the COVID-19 Pandemic, with a Focus on the Effects of Animal Assisted Activities

Abstract: The COVID-19 pandemic has caused extreme deviations from everyday life. The aim of this study was to investigate how these deviations affected adolescents’ sense of coherence and their level of aggression, and whether this was influenced by their relationship with animals, especially horses. In two random samples of students from vocational schools in Hungary, taken in June 2018 and June 2020 (n1 = 525, n2 = 412), separate groups were drawn from those who had regularly engaged in equine-assisted activities (ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
1
0
1
Order By: Relevance
“…Previous studies have shown that a high sense of coherence is related to better health outcomes, and this has been observed in the care of diabetic patients, with neurological diseases, autoimmune diseases, neoplastic diseases, in oral health care and even during the covid-19 pandemic. 57,58 SOC, a construct of Antonovsky 's salutogenic theory, is a personal orientation for identifying, coping and solving problems, which has become a fundamental concept in public health, particularly for health promotion. 59 Antonovsky 's inspiration for researching this phenomenon came when he studied climacteric women who had lived in concentration camps during World War II, finding that some of them maintained good physical and mental health.…”
Section: Reflections On the Role Of The Caregiver In Integration With...mentioning
confidence: 99%
“…Previous studies have shown that a high sense of coherence is related to better health outcomes, and this has been observed in the care of diabetic patients, with neurological diseases, autoimmune diseases, neoplastic diseases, in oral health care and even during the covid-19 pandemic. 57,58 SOC, a construct of Antonovsky 's salutogenic theory, is a personal orientation for identifying, coping and solving problems, which has become a fundamental concept in public health, particularly for health promotion. 59 Antonovsky 's inspiration for researching this phenomenon came when he studied climacteric women who had lived in concentration camps during World War II, finding that some of them maintained good physical and mental health.…”
Section: Reflections On the Role Of The Caregiver In Integration With...mentioning
confidence: 99%
“…A serdülők számára is megrázók voltak a naponta érkező hírek a növekvő járványról és a halálesetek számának növekedéséről, ami a közvetlen környezetükben is megnyilvánult. A COVID-19 pandémia serdülők életére gyakorolt hatásairól szóló 11 tanulmány áttekintése (Tóth et al, 2022) azt mutatta, hogy a világjárvány a serdülők életének különböző dimenzióit befolyásoló meghatározó tényezőnek tekinthető (Oliveira et al, 2020). Ezt az eredményt erősítették meg más tanulmányok is, amelyek a lezárás során e korcsoportban jelentkező különféle pszichológiai tünetekről és viselkedésbéli változásokról szóltak (Francisco et al, 2020;Jiao et al, 2020).…”
Section: A Covid-19 Pandémia Hatása a Serdülők Mindennapjairaunclassified